Sweetpotatoes [Ipomoea batatas (L.) lam]: the super food of the Next Century? An intensive review on their potential as a sustainable and versatile food source for future generations - Shahidul Islam (CyTA - Journal of Food)
This review article explores various aspects of sweetpotatoes and their leaves, including their production, nutritional composition, health benefits, culinary uses, and future potential as a superfood. Often hailed as a nutrient powerhouse, sweetpotatoes have recently gained popularity due to their exceptional dietary profile and culinary versatility. As a starchy root vegetable from the Convolvulaceae family, sweetpotatoes are consumed worldwide and are integral to many cultures and cuisines. Their vibrant colors, ranging from orange to purple, enhance visual appeal and signal their rich nutritional value. Sweetpotatoes contribute significantly to human health, solidifying their status as a superfood. With endless culinary possibilities, they are an essential addition to a well-balanced diet. Looking ahead, research and innovation aim to enhance sweetpotatoes’ nutritional value, develop climate-resilient genotypes, and promote sustainable production, ultimately contributing to food security, economic growth, and healthier diets globally. The expanding market underscores the urgency of prioritizing these research areas.